Mathematical algorithms of software for numerical simulation of aberrated laser beam propagation - Čiegis, R.; Kairytė, G.; Dement'ev, A. (Mathematical Modelling and Analysis, 1996)
“Mathematical algorithms of software for numerical simulation of aberrated laser beam propagation” Mathematical Modelling Analysis, 1(1), p. 58-62. First Published Online: 14 Oct 2010